Świat stworzony znakiem Boga i samotności człowieka w świetle X księgi "Wyznań" św. Augustyna – próba interpretacji - Terka, Mariusz (Vox Patrum, 2024)
This article is an attempt to answer the question about the world created, which pointing to God also becomes a sign of the loneliness of man seeking Him. The reflections were based on the analysis of Book X of the Confessions of St. Augustine. The article is divided into four parts. In the first, the theory of the sign was shown, which refers to the thing it signifies, but assumes knowledge of it. Without knowledge of things, the sign is incomprehensible. The second part describes the beginning of the journey of seeking God, which is the question of love for Him. Man seeks God as the object of his love and turns to creatures. He receives two answers: “We are not your God” and “He created us”. The third part presents the world as a sign that speaks through the beauty of the world and points to the Creator, and the man who admires the beauty of creatures becomes a lover of God. The fourth part shows that the world is a sign that prevents us from meeting God and satisfying the thirst for love. The created world becomes a sign of man’s loneliness, awakening in the encounter of love seeking God with the world’s negative response.